1988
DOI: 10.1111/j.1365-2621.1988.tb07847.x
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning Behavior and Off‐Flavor Thresholds in Cookies from Plastic Packaging Film Printing Ink Compounds

Abstract: Absolute off-flavor thresholds were determined for six solvents in a high fat cookie by a combination of sensory evaluation and gas chromatographic analysis for solvents. Thresholds at 25°C were toluene (1.2 ppm), butanone-2 (5 ppm), ethyl acetate (7 ppm), hexane (24 ppm), propanol-2 (37 ppm), 2-methoxy ethanol (63 ppm). Partition coefficients were also determined for these solvents in the cookies and in polypropylene packaging film to estimate the concentration in the film that could produce off-flavor in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…THE PARTITIONING BEHAVIOR and absolute flavor thresholds of six ink solvents in cookies was recently reported (Halek and Hatzidimitriu, 1988;Halek and Levinson, 1988). The results showed that threshold values varied among these compounds but did not show specific patterns for structural or functional features that would explain the variations.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…THE PARTITIONING BEHAVIOR and absolute flavor thresholds of six ink solvents in cookies was recently reported (Halek and Hatzidimitriu, 1988;Halek and Levinson, 1988). The results showed that threshold values varied among these compounds but did not show specific patterns for structural or functional features that would explain the variations.…”
Section: Introductionmentioning
confidence: 63%
“…The cookie, in addition to its mixture of carbohydrates, proteins, fats, salt and water, has physical structural features such as sugar bridges resulting from the baking process. As previously described (Halek and Levinson, 1988), compositional differences in foods have given wide differences in the threshold values for a given compound. Comparison of properties of molecular weights, boiling points, vapor pressures, solubilities and dipole moment showed no trends to explain the positions on the threshold scale.…”
Section: Apparatusmentioning
confidence: 95%
“…The results indicate that the partition coefficient values at a 1-MCP concentration of 142 g were not significantly different from values at 35, 66, 94, and 121 g of 1-MCP, and thus show that the partition coefficients were not significantly affected by the concentration of 1-MCP. Halek (1988) reported that partition coefficient values were dependent on the concentration in a substrate between a cookie (or film) and air in a closed vial. Kieckbusch (1979) measured the partition coefficients of acetates in sucrose solutions at different temperatures and concentrations.…”
Section: Partition Coefficientmentioning
confidence: 99%
“…The partition coefficient values of paper, Tyvek, and LDPE were close to zero, respectively, and thus no adsorption occurred. Halek (1988) indicated that isotatic polypropylene film had a higher affinity for hexane and toluene and a lower affinity for oxygenated compounds in an air system. Gavara (1996) reported that polystyrene film had high partition coefficient values for toluene in water/polystyrene systems.…”
Section: Partition Coefficientmentioning
confidence: 99%
“…Several studies reported the partitioning behaviour (An & Halek, 1996;Halek & Chan, 1994;Halek & Levinson, 1988.…”
Section: Introductionmentioning
confidence: 97%